Pablo Picasso : a contemporary dialogue. - Baechler, Donald; Baude, Dawn Michelle; Halley, Peter; Lafontaine, Marie-Jo; Picasso, Sydney; Ropac, Thaddaeus; Rosenblum, Robert; Salzmann, Günter; Serra, Richard; Stuart, Elizabeth; Galerie Thaddaeus Ropac, Salzburg (Salzburg : Galerie Thaddaeus Ropac, 1996)
Baechler, Donald ; Balkenhol, Stephan ; Barcelo, Miquel ; Barney, Matthew ; Baselitz, Georg ; Bianchi, Domenico ; Chia, Sandro ; Clemente, Francesco ; Condo, George ; Cucchi, Enzo ; Galan, Julio ; Halley, Peter ; Hockney, David ; Johns, Jasper ; Lafontaine, Marie-Jo ; Lichtenstein, Roy ; Lüpertz, Markus ; Paladino, Mimmo ; Picasso, Pablo ; Schnabel, Julian ; Serra, Richard ; Sherman, Cindy ; Taaffe, Philip
biog. per kunstenaar p. 144-156
Engels
Pablo Picasso : A contemporary dialogue, Galerie Thaddaeus Ropac Salzburg, 20 July - 31 August, 1996
boek
Keywords: Picasso, Pablo